Clinical and prognostic implications of RET rearrangements in metastatic lung adenocarcinoma patients with malignant pleural effusion. Issue 2 (May 2015) - Tsai, Tzu-Hsiu; Wu, Shang-Gin; Hsieh, Min-Shu; Yu, Chong-Jen; Yang, James Chih-Hsin; Shih, Jin-Yuan
Highlights We screened RET-rearranged NSCLC using multiplex RT-PCR for 722 effusion samples. Seventeen (2.4%) KIF5B–RET and CCDC6–RET fusions were detected, including two novel variants. Presence of RET rearrangements was not associated with age, sex, or smoking history. Solid histologic subtype accounted for the majority of RET-rearranged tumors. RET-rearranged NSCLC conferred favorable survival comparable to EGFR-mutant tumors.